Testosterone Therapy on Active Surveillance and Following Definitive Treatment for Prostate Cancer - Golla, Vishnukamal (Curr Urol Rep, 2017)
PURPOSE OF REVIEW: Previously considered an absolute contraindication, the use of testosterone therapy in men with prostate cancer has undergone an important paradigm shift. Recent data has changed the way we approach the treatment of testosterone deficiency in men with prostate cancer. In the current review, we summarize and analyze the literature surrounding effects of testosterone therapy on patients being treated in an active surveillance protocol as well as following definitive treatment for prostate cancer. RECENT FINDINGS: The conventional notion that defined the relationship between increasing testosterone and prostate cancer growth was based on limited studies and anecdotal case reports. Contemporary evidence suggests testosterone therapy in men with testosterone deficiency does not increase prostate cancer risk or the chances of more aggressive disease at prostate cancer diagnosis. Although the studies are limited, men who received testosterone therapy for localized disease did not have higher rates of recurrences or worse clinical outcomes. Current review of the literature has not identified adverse progression events for patients receiving testosterone therapy while on active surveillance/watchful waiting or definitive therapies. SUMMARY: The importance of negative effects of testosterone deficiency on health and health-related quality of life measures has pushed urologists to re-evaluate the role testosterone plays in prostate cancer. This led to a paradigm shift that testosterone therapy might in fact be a viable option for a select group of men with testosterone deficiency and a concurrent diagnosis of prostate cancer.